Microstructure and mechanical properties of Ti60–Ti2AlNb functionally graded materials fabricated by laser directed energy deposition - Yaguang Wang; Shuai Liu; Yasong Tan; Meng Wang; Shufan Xian; Xueping Li; Qian Wang; Jiabao Guo; Xin Lin; Weidong Huang (Journal of Materials Research and Technology)
The increasing demands for materials that service under high temperature environments in advanced aero-engines with high thrust-to-weight ratios have led to the exploration of functionally graded materials, which can offer unique advantages for addressing these challenges, such as the ability to achieve multiple properties at different positions of the components. In this study, Ti60–Ti2AlNb functionally graded materials were fabricated via laser directed energy deposition (L-DED) with 20% compositional step and various step widths in the transition zone. The distribution of chemical composition, microstructure, and microhardness in the transition zone of functionally graded materials with different compositional paths along the deposition direction were investigated. Meanwhile, the mechanical properties and fracture mechanisms were also evaluated. Smooth composition transition has been achieved in the joint zone between Ti60 and Ti2AlNb. By decreasing the width of each composition zone in the transition area or removing the Ti60-60% Ti2AlNb zone, the precipitation of the hard and brittle α2 phase can be effectively suppressed, thereby enhancing the tensile strength of the graded material. Through this approach, Ti60–Ti2AlNb functionally graded material with a tensile strength of 1030.9 MPa and elongation of 2.0% was fabricated.